Pengaruh Kombinasi Balutan Poliuretan dan Sirih Merah Terhadap Tingkat Infeksi pada pasien Ulkus Diabetik - Silalahi, Rini Debora; Tane, Reisy (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2024)
Diabetic ulcers are a common clinical problem in patients with diabetes mellitus. Infected diabetic foot wounds will complicate the healing process, resulting in prolonged healing time. One important factor in reducing the rate of diabetic foot wound infection is the right choice of dressings that suit the needs of the wound. Polyurethane dressings affect the absorption of chronic wound exudate and the growth of tissue granulation. In this study, polyurethane dressings were combined with red betel leaves which have antimicrobial properties. This study aims to identify the effect of polyurethane (PU) dressings on reducing infection rates in diabetic ulcer patients. This study is a quantitative study using a quasi-experimental design with a control group. The number of respondents in this study was 23 people in the intervention group and 23 people in the control group with inclusion criteria for clients with grade 1-4 diabetic ulcers, random blood sugar <200 mg/dl, not undergoing diabetic ulcer treatment, and willing to be treated with a combination of polyurethane dressing and red betel leaves wound care techniques. The results showed that compared to patients who were given simple sterile dressings, patients who were given polyurethane dressings had a lower wound infection rate (p = 0.001). The conclusion of this study is that polyurethane dressings can reduce the rate of wound infection, and shorten healing time, so this wound care method can be applied in wound nursing practice.